High-intensity interval training and hypertension: Maximizing the benefits of exercise? - Ciolac, Emmanuel Gomes [UNESP] (My University, 2012)
Essential arterial hypertension is the most common risk factor for cardiovascular morbidity and mortality. Regular exercise is a well-established intervention for the prevention and treatment of hypertension. Continuous moderate-intensity exercise training (CMT) that can be sustained for 30 min or more has been traditionally recommended for hypertension prevention and treatment. On the other hand, several studies have shown that high-intensity interval training (HIT), which consists of several bouts of high-intensity exercise (~85% to 95% of HRMAX and/or VO2MAX lasting 1 to 4 min interspersed with intervals of rest or active recovery, is superior to CMT for improving cardiorespiratory fitness, endothelial function and its markers, insulin sensitivity, markers of sympathetic activity and arterial stiffness in hypertensive and normotensive at high familial risk for hypertension subjects. This compelling evidence suggesting larger beneficial effects of HIT for several factors involved in the pathophysiology of hypertension raises the hypothesis that HIT may be more effective for preventing and controlling hypertension.
Keywords: Exercise; Hypertension; Autonomic nervous system; Endothelial function; Arterial stiffness